Photoluminescence investigations of ZnO micro/nano structures - Rodrigues, J. (2021)
Zinc oxide (ZnO) is probably one of the most researched wide bandgap semiconductors in the last decades due to its unique characteristics in terms of low production cost, high availability, bioinertness, and especially its interesting optical properties. Although this semiconductor is considered an ‘old’ material and is known to possess such unique properties for more than three decades, the interest was renewed because of the advances in nanotechnology and the possibility to be produced in a vast number of nanostructures with tunable properties. An adequate knowledge of the nanomaterials’ optical response is mandatory for assessing and optimizing their functionalities towards different applications. Although the photoluminescence properties of ZnO bulk materials have been known from several decades, quite a number of open questions remains, namely regarding the nature of defects responsible for the broad luminescence bands frequently observed in the visible spectral region. With the effects of reducing the dimensionality of the material to the nanoscale, changes may arise in the luminescence outcome due to the role of the surface/interface characteristics. Indeed, the surface phenomena can strongly affect the nanostructure properties and can be used to tailor them, consequently having a profound influence on the performance of the devices where the nanostructures are employed. Hence, in this article, an overview of the fundamental properties of ZnO, with emphasis on the main optical recombination mechanisms, both in bulk and at the nanoscale, is provided to disclose some of the current knowledge in this subject. In addition, some examples of the myriad of applications where this semiconductor has been exploited are also discussed.